Low-wage careers: Are there dead-end firms and dead-end jobs? - Alexander Mosthaf; Claus Schnabel; Jens Stephani (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
Using representative linked employer-employee data of the German Federal Employment Agency, this paper shows that just one out of seven full-time employees who earned low wages (i.e., less than two-thirds of the median wage) in 1998/99 was able to earn wages above the low-wage threshold in 2003. Bivariate probit estimations with endogenous selection indicate that upward wage mobility is higher for younger and better qualified low-wage earners, whereas women are substantially less successful. We show that the characteristics of the employing firm also matter for low-wage earners' probability of escaping low-paid work. In particular, small plants and plants with a high share of low-wage earners often seem to be dead ends for low-wage earners. The likelihood of leaving the low-wage sector is also low when staying in unskilled and skilled service occupations and in unskilled commercial and administrative occupations. Consequently, leaving these dead-end plants and occupations appears to be an important instrument for achieving wages above the low-wage threshold.
Keywords: J30; J60; 330; IAB-Linked-Employer-Employee-Datensatz; Niedriglohn; berufliche Mobilität; Arbeitskräftemobilität; beruflicher Aufstieg; berufliche Qualifikation; geschlechtsspezifische Faktoren; Frauen; Kleinbetrieb; Geringverdiener